Matrilineal memory and patrilineal constraint: Women’s entrepreneurial practices as living cultural heritage in coastal Indonesia - Dalimunthe, Ritha F; Nauly, Meutia; Dwiningrum, Siti Irene Astuti; Siregar, Muhammad Bangun; Jendrius; Ramadani (Research Journal in Advanced Humanities, 2026)
This study examines how ethnic cultural structures, gendered practices, and communal networks shape the lived experiences of women in three coastal communities in Indonesia: Melayu in Medan Belawan, Javanese in Bantul, and Minangkabau in Agam. Drawing on ethnographic surveys, in-depth interviews, and focus group discussions, the research explores how women navigate traditional roles, inheritance systems, and community norms to maintain social cohesion and cultural continuity. Findings reveal that women play central roles in preserving and transmitting cultural practices, such as mutual aid (gotong royong), matrilineal inheritance, and ritualized economic activities, while adapting to modern technologies like social media to sustain community networks. The study highlights the intersection of cultural heritage, gender, and social adaptation, demonstrating how women actively mediate between tradition and modernity. These insights contribute to understanding coastal communities as living heritage sites, where cultural norms and gendered practices underpin social resilience and communal identity.